2017
DOI: 10.1016/j.ygcen.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Stress-responsiveness influences baseline glucocorticoid levels: Revisiting the under 3 min sampling rule

Abstract: Plasma glucocorticoid (CORT) levels collected within 3min of capture are commonly believed to reflect pre-stressor, baseline CORT levels. Differences in these "baseline" values are often interpreted as reflecting differences in health, or the amount of social and environmental stress recently experienced by an individual. When interpreting "baseline" values it is generally assumed that any effect of capture-and-handling during the initial sampling period is small enough and consistent enough among individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 128 publications
2
20
0
Order By: Relevance
“…These authors concluded that sampling should occur within 2 min of capture, with 3 min being the uppermost limit (Romero and Reed 2005). Small et al (2017) came to similar conclusions (ϳ2 min). Within the teleost literature, most blood samples appear to be collected within 3 min of the animal's capture (e.g., Knapp and Neff 2007;Cook et al 2012).…”
Section: Introductionmentioning
confidence: 68%
“…These authors concluded that sampling should occur within 2 min of capture, with 3 min being the uppermost limit (Romero and Reed 2005). Small et al (2017) came to similar conclusions (ϳ2 min). Within the teleost literature, most blood samples appear to be collected within 3 min of the animal's capture (e.g., Knapp and Neff 2007;Cook et al 2012).…”
Section: Introductionmentioning
confidence: 68%
“…We also recorded the length of the standardized period of restraint used prior to collecting a blood sample for stress-induced GCs. The time between stressor exposure and peak stress-induced GCs varies across species and individuals, and most species peak after 14-60 minutes of restraint (Breuner et al ., 2008; Satterthwaite et al ., 2010; Small et al ., 2017). We chose to accept authors’ selected timeframes as an acceptable measure for stress-induced GCs.…”
Section: Methodsmentioning
confidence: 99%
“…To enable spatial discrimination, navigation objects with differing shape and color were placed outside of the left and right arm of the arena. The whole process from cage opening to collection of the last drop was carried out within less than 1.5 minutes to avoid a procedure-associated rise of corticosterone [37]. Plasma aliquots were frozen immediately.…”
Section: Alternations T-mazementioning
confidence: 99%